2017
DOI: 10.1073/pnas.1708852114
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into binding of STAC proteins to voltage-gated calcium channels

Abstract: SignificanceSkeletal muscle contraction is a tightly orchestrated event that starts with the depolarization of the T-tubular membrane. At the center is a functional and mechanical coupling between two membrane proteins: L-type voltage-gated calcium channels, located in the plasma membrane, and ryanodine receptors, located in the membrane of the sarcoplasmic reticulum. How exactly these proteins associate has remained a mystery, but recent reports have highlighted a key role for the STAC3 adaptor protein in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
123
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(132 citation statements)
references
References 38 publications
6
123
2
1
Order By: Relevance
“…Indeed, in a recent X-ray analysis study, we solved the structure of tandem-SH3 domains of STAC in complex with the II-III loop of Ca V 1.1. Introducing the NAM mutation in the SH3-1 domain or mutations in the corresponding binding site of the II-III loop both abolished the interaction and impaired EC coupling (6). However, we and others previously showed that the NAM mutation in STAC3 did not prevent STAC3-Ca V 1.1 association in skeletal myotubes (2-4, 7).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Indeed, in a recent X-ray analysis study, we solved the structure of tandem-SH3 domains of STAC in complex with the II-III loop of Ca V 1.1. Introducing the NAM mutation in the SH3-1 domain or mutations in the corresponding binding site of the II-III loop both abolished the interaction and impaired EC coupling (6). However, we and others previously showed that the NAM mutation in STAC3 did not prevent STAC3-Ca V 1.1 association in skeletal myotubes (2-4, 7).…”
Section: Discussionmentioning
confidence: 74%
“…First, while we demonstrated that STAC3 interacts with Ca V 1.1 as stably as the β 1a subunit (7), the measured affinity of the STAC SH3-1/II-III loop interaction is more than 100-fold weaker, suggesting that this site alone would not be sufficient for a stable interaction (6). Second, the four IQ residues critical for the STAC interaction are conserved among the IQ domains of Ca V 1.1 and Ca V 1.2, and mutation of three residues not conserved between these two isoforms did not weaken the STAC3/ Ca V 1.2 complex (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations